Design of Website-Based Tourism Travel Information System (Case Study : Tenta Tour) - Kawi, R. Gibranto; Suprihadi (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The Information System Design for the Tenta Tour Application, hosted on a website, is a critical component of modern tourism services. This research employs the rigorous Black Box Testing methodology to comprehensively evaluate the application's functionality, disregarding its internal structure. The study focuses on identifying potential errors and areas for improvement to enhance the quality and reliability of the system in delivering travel services to users. Through systematic Black Box Testing, the research investigates the Tenta Tour Application Information System on the web platform, with a primary emphasis on functionality rather than delving into the intricacies of the internal system structure. Test data is meticulously analyzed to uncover potential errors and opportunities for enhancements, all aimed at elevating the reliability and quality of travel services. The research findings successfully meet established criteria by effectively identifying potential functional errors within the Tenta Tour Application Information System when deployed on a website. The application of the Black Box Testing methodology has proven instrumental in uncovering functional issues that can be proactively addressed. These discoveries constitute a substantial contribution to enhancing the reliability and overall quality of travel services accessible through the application. In conclusion, this research underscores the efficacy of the Black Box Testing method in assessing the Tenta Tour Application Information System hosted on a website. The test results have proficiently identified potential functional errors and provided invaluable insights to enhance the application's reliability. The implementation of improvements informed by these findings is anticipated to significantly raise the standard of travel services rendered through this platform.